Do outcomes diverge over time? A 5-year Spine CORe™ Quality Outcomes Database study comparing patient-reported outcomes after minimally invasive versus open surgery for degenerative grade 1 lumbar spondylolisthesis - Farhan A. Khan; Peter J. Chabot; Dean Chou; Praveen V. Mummaneni; Mohamad Bydon; Erica F. Bisson; Christopher I. Shaffrey; Steven D. Glassman; Kevin T. Foley; Eric A. Potts; Chun-Po Yen; Paul K. Kim; et al. (Journal of Neurosurgery: Spine, 2026)
OBJECTIVE Both open and minimally invasive surgery (MIS) approaches for degenerative low-grade lumbar spondylolisthesis have been shown to improve patient-reported outcomes (PROs). Recent studies, however, have suggested that MIS may offer superior, more durable benefits due to less soft tissue dissection and expedited recovery. Unfortunately, data demonstrating whether or when such divergences in long-term PROs may arise are limited. METHODS The authors utilized the prospective multicenter Spine CORe™ Quality Outcomes Database grade 1 lumbar spondylolisthesis dataset to evaluate longitudinal outcomes over 60 months. PROs included Oswestry Disability Index (ODI), EuroQol-5D, and numeric rating scale for back pain and leg pain scores. Outcomes were compared between MIS and open approaches using univariate and multivariable analyses. Minimal clinically important differences (MCIDs) were assessed using established thresholds. RESULTS Of 608 patients, 265 (43.6%) underwent MIS while 343 (56.4%) underwent open surgery. MIS patients were older (64.1 ± 11.6 vs 60.7 ± 12.2 years, p < 0.001) and had lower BMI (29.7 ± 5.8 vs 30.9 ± 6.7 kg/m 2 , p = 0.0180). Overall, 72.8% of MIS and 80.2% of open patients underwent arthrodesis (p = 0.0330). Other variables, including baseline PROs, were similar. After surgery, MIS was associated with less blood loss (104.2 ± 100.4 vs 249.1 ± 233.3 mL, p < 0.001) and shorter length of stay (2.3 ± 1.9 vs 3.1 ± 1.7 days, p < 0.001); there were no differences in readmission, complication, or 60-month related reoperation rates. In univariate analyses, at the 3-month and 12-month follow-ups, there were no differences in magnitude of change or MCID achievement for any PRO. MIS, however, demonstrated superior improvements in ODI score at 24 months (−25.8 ± 20.6 vs −20.9 ± 20.0, p = 0.0116) and 60 months (−24.4 ± 20.9 vs −19.8 ± 21.1, p = 0.0162), with greater MCID rates (24 months: 72.8% vs 61.1%, p = 0.0090; 60 months: 68.1% vs 58.8%, p = 0.0363). After multivariable analysis, these significant differences in ODI score persisted (24-month change: β = −6.2, p = 0.0014; 60-month change: β = −4.6, p = 0.0216; 24-month MCID: OR 2.0, p = 0.0022; 60-month MCID: OR 1.6, p = 0.0302). After stratification, these multivariable results were consistent in patients undergoing arthrodesis but not in those undergoing decompression alone. CONCLUSIONS In this prospective multicenter study, there were no differences in early disability or quality of life outcomes between MIS and open surgery for low-grade spondylolisthesis. By 24 months, trajectories diverged: MIS yielded greater improvements in ODI score that persisted at the 60-month follow-up, especially with arthrodesis. While open surgery remains essential in many contexts, MIS may offer more meaningful long-term improvement in appropriately selected patients.